Objetos de aprendizagem e alfabetização: a proposição de um encontro - Gallo, Patricia (2011)
This study investigates the development of Learning Objects for the literacy of children. It aims to know based in the notion of literacy teachers the main factors of academic failure in literacy and researching in Brazil, as well as identify relevant activities in the literacy process of children to support the creation of a set of Learning Objects. Refers to an exploratory research, which is configured as a qualitative nature case study, inspired in part in an action-research described by Thiollent (2003), conducted with ten early grades elementary school teachers of a public municipal school in Parnamirim / RN. As methodological options for data collection uses questionnaires and focuses on the group of teachers, analyzing the data, referring back to the ideas by Szymanski (2001; 2008) and content analysis, guided by Bardin (2002). The development of Learning Objects, follows the steps of development suggested by Garrett (2000). Rules in its multidisciplinary theoretical reference and promotes a conceptual dialogue on: Literacy; Literacy School Failure; Pedagogical Practice in Literacy; Thoughts and Language; Multimedia and Hypermedia; Learning Objects. Perceives that the act of education in literacy as an act of love, courage and social interaction between individuals - educator and pupil, so there is ownership of the object of knowledge in the relations with the world and with the experience, through a pedagogical practice that assumes all different knowledges, the moral political ideal, the mindsets of the students, and can make use of teaching materials that supports the learning process and are consistent with the educational objectives (FREIRE, 1998; FREINET, 1976; VYGOTSKY, 1998; FERREIRO AND TEBEROSKY, 1985; JONASSEN, 2000; WILEY, 2001). Figures out, through the teachers' opinions, five reasons for school failure in literacy, three inside the school environment: teacher; academic assistant and principal; student, and two outside the school environment: parents/family; government and public management. Presents a set of Learning Objects, based on the constructivist thought, developed from the identification of activities considered relevant by teachers in literacy's teaching and learning process. Suggests the use of Learning Objects as pedagogical practice in literacy as a digital resource that supports learning and can trigger important cognitive processes for the acquisition of reading and writing skills in the school environment